At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer: I hope this helps! :)
x = -3
- rearrange terms: 6x+12/3 = 5-9/2
- subtract the numbers: 6x+12/3 = -4/2
- eliinate fractions denominators: 3 times 6x+12/3 = 3(-2)
- simplify fractions: 6x+12/3 = -2
- eliinate fractions denominators: 3 times 6x+12/3 = 3(-2)
- multiplt the numbers: 6x + 12 = -6
- subtract 12 from both sides of the equation: 6x + 12-12 = -6-12
- simplify: 6x = -18
- divide both sides of the equation by the same factor: 6x/6 = -18/6
- x = -3
Answer: x=-3
Answer:
- [tex]x = -3[/tex]
Step-by-step explanation:
- [tex]\frac{12 + 6x}{3} = \frac{5 - 9}{2}[/tex]
- => [tex]2(12 + 6x) = 3(5 - 9)[/tex]
- => [tex]24 + 12x = 15 - 27[/tex]
- => [tex]24 + 12x = -12[/tex]
- => [tex]24 + 12 = -12x[/tex]
- => [tex]36 = -12x[/tex]
- => [tex]x = -3[/tex]
Conclusion:
Therefore, x = -3
Hoped this helped.
[tex]GeniusUser[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.